Incidencia socioeconómica de la pandemia la COVID-19 en las exportaciones de la Empresa AGROASEMAD CIA.LTDA en el año 2021 - Mendoza Segura, Rosa Geomayra (2023)
The objective of this degree work is to determine the degree of socioeconomic incidence that the COVID 19 pandemic produced as a collateral effect in the export area of the company AGROASEMAD CÍA. LTDA and for this a survey of information was carried out which was achieved through a literature review that through a quantitative approach determined the great negative impact that occurred in the export area within the cocoa sector of Ecuador and as a reflection of this incidence the results obtained shows a directly proportional relationship in terms of production and the critical months of the health emergency. In other words, the time when the pandemic was located in the most critical moments, the level of exports was much lower, reaching the point of having a drop of approximately 25 tons of product per month, which directly affected the stability of the company and on the other hand, when the pandemic was controlled, the level of exports reached high levels to the point that exports of up to 100 tons of products were registered, which led to a good end of the year for the company.